Fig latex inhibits the growth of pathogenic bacteria invading human diabetic wounds and accelerates wound closure in diabetic mice - Salah, Mohamed; Badr, Gamal; Hetta, Helal F.; Khalifa, Walaa A.; Shoreit, Ahmed A. (Scientific reports, 2022)
Impaired wound healing is one of the most critical complications associated with diabetes mellitus. Infections and foot ulcers are major causes of morbidity for diabetic patients. The current treatment of diabetic foot ulcers, commonly used antibiotics, is associated with the development of bacterial resistance. Hence, novel and more effective natural therapeutic antibacterial agents are urgently needed and should be developed against the pathogenic bacteria inhabiting diabetic wounds. Therefore, the current study aimed to investigate the impact of fig latex on pathogenic bacteria and its ability to promote the healing process of diabetic wounds. The pathogenic bacteria were isolated from patients with diabetic foot ulcers admitted to Assiut University Hospital. Fig latex was collected from trees in the Assiut region, and its chemical composition was analyzed using GC‒MS. The antibacterial efficacy of fig latex was assessed on the isolated bacteria. An in vivo study to investigate the effect of fig latex on diabetic wound healing was performed using three mouse groups: nondiabetic control mice, diabetic mice and diabetic mice treated with fig latex. The influence of fig latex on the expression levels of β-defensin-1, PECAM-1, CCL2 and ZO-1 and collagen formation was investigated. The GC‒MS analysis demonstrated the presence of triterpenoids, comprising more than 90% of the total latex content. Furthermore, using a streptozotocin-induced diabetic mouse model, topical treatment of diabetic wound tissues with fig latex was shown to accelerate and improve wound closure by increasing the expression levels of β-defensin-1, collagen, and PECAM-1 compared to untreated diabetic wounds. Additionally, fig latex decreased the expression levels of ZO-1 and CCL2.